Analysis of the autoproteolytic activity of the recombinant helper component proteinase from zucchini yellow mosaic virus - Kajohn Boonrod; Füllgrabe, Marc W.; Krczal, Gabi; Wassenegger, Michael (Biological chemistry, 2011)
The multifunctional helper component proteinase (HC-Pro) of potyviruses contains an autoproteolytic function that, together with the protein 1 (P1) and NIa proteinase, processes the polyprotein into mature proteins. In this study, we analysed the autoproteolytic active domain of zucchini yellow mosaic virus (ZYMV) HC-Pro. Several Escherichia coli -expressed MBP:HC-Pro:GFP mutants containing deletions or point mutations at either the N- or C-terminus of the HC-Pro protein were examined. Our results showed that amino acids essential for the proteolytic activity of ZYMV HC-Pro are distinct from those of the tobacco etch virus HC-Pro, although the amino acid sequences in the proteolytic active domain are conserved among potyviruses.
Gesehen am 02.06.2022